Electrophilicity and Solvatochromic Reversal of Pyridinium Phenolate Betaine Dyes - Caroli-Rezende, M; Aracena-Astudillo, A; Aracena-Astudillo, A (2012)
The solvatochromic reversal of phenolate betaine dyes may be theoretically rationalized and predicted by determining the flow direction of their internal charge-transfer in media of increasing polarity, with the aid of the electrophilicities of the donor and acceptor moieties, or of the corresponding electrophilic Fukui functions. The protocol was applied to ten examples from the literature. © 2012 Elsevier B.V. All rights reserved.